Arterial Injury and Endothelial Repair: Rapid Recovery of Function after Mechanical Injury in Healthy Volunteers - Lindsey Tilling; Joanne Hunt; Ann Donald; Brian Clapp; Phil Chowienczyk (Cardiology Research and Practice)
Objective. Previous studies suggest a protracted course of recovery after mechanical endothelial injury; confounders may include degree of injury and concomitant endothelial dysfunction. We sought to define the time course of endothelial function recovery using flow-mediated dilation (FMD), after ischaemia-reperfusion (IR) and mechanical injury in patients and healthy volunteers. The contribution of circulating CD133+/CD34+/VEGFR2+ “endothelial progenitor” (EPC) or repair cells to endothelial repair was also examined. Methods. 28 healthy volunteers aged 18–35 years underwent transient forearm ischaemia induced by cuff inflation around the proximal biceps and radial artery mechanical injury induced by inserting a wire through a cannula. A more severe mechanical injury was induced using an arterial sheath and catheter inserted into the radial artery of 18 patients undergoing angiography. Results. IR and mechanical injury produced immediate impairment of FMD (from 6.5 ± 1.2% to 2.9 ± 2.2% and from 7.4 ± 2.3% to 1.5 ± 1.6% for IR and injury, resp., each P<0.001) but recovered within 6 hours and 2 days, respectively. FMD took up to 4 months to recover in patients. Circulating EPC did not change significantly during the injury/recovery period in all subjects. Conclusions. Recovery of endothelial function after IR and mechanical injury is rapid and not associated with a change in circulating EPC.